2012
DOI: 10.1152/ajpcell.00289.2011
|View full text |Cite
|
Sign up to set email alerts
|

Human gene SLC41A1 encodes for the Na+/Mg2+ exchanger

Abstract: Magnesium (Mg(2+)), the second most abundant divalent intracellular cation, is involved in the vast majority of intracellular processes, including the synthesis of nucleic acids, proteins, and energy metabolism. The concentration of intracellular free Mg(2+) ([Mg(2+)](i)) in mammalian cells is therefore tightly regulated to its optimum, mainly by an exchange of intracellular Mg(2+) for extracellular Na(+). Despite the importance of this process for cellular Mg(2+) homeostasis, the gene(s) encoding for the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(168 citation statements)
references
References 53 publications
(91 reference statements)
2
164
1
Order By: Relevance
“…The absorbed magnesium is then extruded via a recently identified magnesium/sodium exchanger SLC41A1 family (89)(90)(91)(92) across the basolateral membrane (93). Interestingly, mutations in SLC41A1 result in a nephronophthisis-like phenotype (93).…”
Section: Renal Regulation Of Magnesiummentioning
confidence: 99%
“…The absorbed magnesium is then extruded via a recently identified magnesium/sodium exchanger SLC41A1 family (89)(90)(91)(92) across the basolateral membrane (93). Interestingly, mutations in SLC41A1 result in a nephronophthisis-like phenotype (93).…”
Section: Renal Regulation Of Magnesiummentioning
confidence: 99%
“…SLC41A1, a member of the solute carrier family 41, is a cell membrane protein expressed in various tissues, including heart, brain, kidney, liver, and colon, and has been proposed as one of the candidates for such Mg 2+ transporters. [28][29][30] Although Mg 2+ transport by SLC41A1 has not been fully characterized, Kolisek et al recently reported that the human SLC41A1 gene encodes for the Na + /Mg 2+ exchanger 4. 28 The finding that mutations of this renal Mg 2+ transporter mimics an NPHP-RC phenotype may be related to the fact that other mutations in proteins involved in renal Mg 2+ transport are known to cause an NPHP-related disorder phenotype.…”
Section: Knockdown Of Slc41a1 In Zebrafish Results In Renal Cystsmentioning
confidence: 99%
“…[28][29][30] Although Mg 2+ transport by SLC41A1 has not been fully characterized, Kolisek et al recently reported that the human SLC41A1 gene encodes for the Na + /Mg 2+ exchanger 4. 28 The finding that mutations of this renal Mg 2+ transporter mimics an NPHP-RC phenotype may be related to the fact that other mutations in proteins involved in renal Mg 2+ transport are known to cause an NPHP-related disorder phenotype. Specifically, recessive mutations of the CLDN16 gene encoding the renal tight junction protein claudin-16 (also called paracellin-1) cause a recessive renal disease that closely mimics NPHP 31 in cattle 24 both clinically and histologically.…”
Section: Knockdown Of Slc41a1 In Zebrafish Results In Renal Cystsmentioning
confidence: 99%
“…Although hypomagnesemia occasionally complicates nonoliguric acute tubular necrosis associated with nephrotoxic drugs, but hypokalemia is accompanied with these conditions. Recently Kolisek et al has reported that the human solute carrier family 41, anion exchanger, member 1[SLC41A1 (mapped on chromosome 1q 31-32)] encodes for the Na + /Mg 2+ exchanger 4 [13] and gain of function mutation of SLC41A1 is associated with Parkinson's disease [14]. But in study by hurd et al, whole-exome capture revealed a homozygous splice acceptor site mutation in the renal Mg 2+ transporter SLC41A1.…”
Section: Discussionmentioning
confidence: 99%